A simulation study of advanced reservation protocol for congestion control in ATM network - Ng, Teng Chuan. (2009)
Advanced Reservation is a variant of Fast Bandwidth Reservation method which has been proposed for Asynchronous Transfer Mode (ATM) network management and congestion control. It allows a burst of data to be scheduled for transmission at a later time when an ATM network is not able to honour the request for transmission instantaneously. A recent simulation study indicates a significant performance advantage of this advanced reservation scheme when compared with the original Fast Bandwidth Reservation using Blocked Call Reject (BCR) Scheme.